Phase Transitions of the BTZ Black Hole in New Massive Gravity - Yun Soo Myung (Advances in High Energy Physics)
We investigate thermodynamics of the BTZ black hole in new massive gravity explicitly. For m2l2>1/2 with m2 being the mass parameter of fourth-order terms and l2 AdS3 curvature radius, the Hawking-Page phase transition occurs between the BTZ black hole and AdS (thermal) soliton. For m2l2<1/2, however, this transition unlikely occurs but a phase transition between the BTZ black hole and the massless BTZ black hole is possible to occur. We may call the latter the inverse Hawking-Page phase transition and this transition is favored in the new massive gravity.